Frequency of Gingival Recession and its Severity - Marij Hameed, Usman Rashid, Syed Midhat Batool, Sarmad Saif, Sadia Rana, Ahmed Umer, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To estimate the frequency of gingival recession and its severity. Study Design: Cross-sectional study Place and Duration of Study: Department of Periodontics, Bakhtawar Amin Medical & Dental College, Multan and Sharif Medical & Dental College Lahore from 1st October 2020 to 30th September 2021. Methodology: Three hundred patients with gingival recession were enrolled. Those patients with a minimum number of permanent twenty teeth and no periodontal therapy were included. The age of the patients was fixed between 15-55 years. A uniform pattern based examination of complete mouth was done. Occlusion trauma assessment was made through analysis of tooth mobility. Results: The mean age was 21.2±2.3 years. Greater number of males such as 60.3% was reported for gingival recession. The age group 46-60 years had a significant difference between recession and without recession cases. The overall frequency of cases with recession was 40.66% and without recession was 59.3%. Conclusion: Gingival recession is considered as multifactorial problem and appearance of it is always the result of more than one contributing factor.